Influence of Temperature and pH on growth and Sporulation of Alternaria alternata incited Alternaria leaf spot in Soybean - R. K. Fagodiya; Amit Trivedi; B. L. Fagodia (Annals of Agricultural Research, 2022)
Soybean (Glycine max L.) is one of the most valuable legume and oil seed crop grown in India with high amount of protein and oil content in it. But in recent time Alternaria leaf spot is one of the major destructive disease of soybean caused by Alternaria alternata in India as well as Rajasthan showing more decline in yield. The fungal pathogen are greatly influenced by environmental factor therefore the present investigation undertaken to effect of temperature and pH on growth/sporulation of A. alternata. It is clearly evident from the result that all the temperature and pH tested showed variation in the diameter of colony and sporulation. The optimum temperature 25ºC and pH 6.5 recorded for better mycelial growth and extent sporulation of A. alternata.